ROLE OF STATE AND WELFARE STATE: FROM COMMONS, KEYNES TO ESPING-ANDERSEN - Nugroho, Wisnu Setiadi (Universitas Muhammadiyah Yogyakarta, 2018)
The welfare state system is a popular economic system nowadays. At least more than fifteen countries have the characteristics of a welfare state economic system with their respective character and features. Esping-Andersen divided the welfare system classification into three major groups, namely the conservative welfare state, socio-democratic welfare state, and liberal welfare state. This article attempts to link the idea and foundation of a welfare state system is two utmost significant economists, John Maynard Keynes and John Roger Commons. Based on history of economic thought, Keynes's thought about the system of welfare states can be seen and traced in the liberal welfare state system on Esping-Andersen classification. On the other hand, traces of Commons' thought can be seen in the socio-democratic state welfare system. Therefore, both Keynes and Commons can be categorized as the founding fathers of the welfare state system. Since their thought about the role of the state is the foundation of welfare state system, long before the United Kingdom began implementing the modern welfare state system in the 1980s. In addition, this study also attempts to undertake comparative analysis of economic systems and present the empirical data on the performance of welfare countries based Esping-Andersen classification in three categories: economic performance, quality health performance, and level of accumulation of human resources. It is hoped that with the facts presented here there will be further discussion regarding the welfare state system.